EXAMINING THE ROLE OF ESG IN REDUCING TAX AVOIDANCE: THE MODERATING EFFECT OF TAX INCENTIVES - Andita, Risma Tesya; Wijayanti, Dwi Marlina (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
The growing attention to corporate responsibility underscores the importance of sustainable business operations, including through incentivized tax systems. This study aims to examine the extent to which firms leverage ESG performance to engage in tax avoidance and how tax incentives promote transparent and sustainable business practices. The research objects are firms listed on the Indonesia Stock Exchange with Thomson Reuters ESG scores for the period 2018-2022. Statistical results indicate no significant relationship between ESG scores for the environmental and governance aspects and tax avoidance. However, there is a significant negative relationship between the social aspect and tax avoidance. Moderated Regression Analysis indicates that tax incentives moderate the ESG components for the environmental and social aspects in relation to tax avoidance. Future research could explore the types of tax incentives most effective at motivating firms to enhance sustainable development without engaging in fraudulent actions. These findings imply that strengthening tax incentive policies can improve corporate compliance and promote sustainable and transparent business behavior.